Trespassing beyond the borders Harriet Ward as writer and commentator on the Eastern Cape frontier - Letcher, Valerie Helen (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1996)
The aim of this thesis is to provide an introduction to the work of writer and journalist Harriet Ward, resident in the Eastern Cape from 1842 to 1848. She was a prolific correspondent to various periodicals published both in South Africa and in London. It would be true to say, to judge from the evidence, that she fulfilled a need felt by the British public for information on life and events in South Africa, and that she became the trusted guide of the middle-class reader. Her range covers reports from the frontiers of war, journalistic articles, memoirs, short stories, novels, autobiography, and editions of other writers' work. After the publication of her articles on the Seventh Frontier War (1846-7), she was recognised and respected as a commentator on the situation at the Eastern Cape, an unusual role for a woman at this time. She was also amongst the foremost victorian women writers published from the early eighteen forties until the end of the eighteen-fifties. Harriet Ward has left a vivid historical and sociological account of the Cape frontier, and her observations and judgements provide a hitherto virtually unknown perspective on an important part of South African history and letters. What makes her even more interesting, as this study seeks to show, is that she was far from conventional in her response to her new environment, both as as a woman and as a representative of a colonialist power. The record she has left of her thoughts on the people, landscape and situations of the time has the capacity to surprise the post-colonial literary critic and historian. Her struggle to find a discursive mode in which to express her consciousness of the oppression, patriarchal and colonial, of the marginalised, whether woman, indigene, Afrikaner, or creole, reveals a significantly transgressive or subversive response to the issues of the day. In re-discovering Harriet Ward, we are forced to reassess our assumptions regarding the period of colonial history to which she was a witness.
Keywords: Ward, Harriet, 1808-1872; Women authors, -- South African -- 19th century -- Biography -- History and criticism; Frontier and pioneer life -- South Africa -- Eastern Cape